Reitzenstein and Qumrân Revisited by an Iranian - Frye, Richard Nelson (Harvard theological review, 1962)
The following remarks are intended to be merely general indications of overall problems which nonetheless, I believe, are necessary before one investigates specific words or concepts which may be borrowed by one culture from another.